Optimistic and pessimistic solutions of the fuzzy shortest path problem by Physarium polycephalum approach. (20th March 2020) - Tuli, Renu; Dadiala, Vini
The remarkable behaviour of Physarium polycephalum has been used to solve the fuzzy shortest path problem. A novel algorithm has been developed for varying degrees of optimism ranging from purely pessimistic to purely optimistic. Providing the decision maker (DM) a range of solutions gives him/her more flexibility in choosing the solution according to his/her degree of optimism. The triangular and trapezoidal fuzzy numbers representing cost or duration of travel are converted to crisp numbers by finding their total integral values and thereafter optimal solutions for varying degrees of optimism are obtained. The process is explained by four numerical examples including a tourist network problem and results obtained are compared with existing work. It is observed that the newly developed algorithm is not only easier to understand and implement but also gives better non-dominated optimal solutions.